Party strength and party weakness in transitional elections: Myanmar's National League for Democracy in 2015. Issue 2 (17th February 2022) - Ladd, Jeremy Martin
ABSTRACT: The National League for Democracy secured an astonishing electoral victory in Myanmar's 2015 general elections after nearly three decades of repression of the party. Despite this victory, there are conflicting accounts on whether the NLD was a strong or a weak party leading into these elections. Appealing to data from an original survey and extensive qualitative field research, this article measures the NLD's strength in 2015 and explores the mechanisms behind it. When operationalized as reported contact with voters, the NLD appears to have been a very strong party, but this strength can be explained by the same widespread enthusiasm for change, for democracy, and for Aung San Suu Kyi that existing scholarship appeals to in explaining the party's victory in general. This finding has important implications for the NLD in the 2020 and future elections, as well as for our understanding of the dynamics of party strength in transitional regimes and new democracies more generally. Most importantly, the strategies parties have employed in transitions are unlikely to be successful in subsequent elections, as widespread enthusiasm and momentum gives way to everyday politics, but newly governing parties are likely to keep appealing to them precisely because they were so successful.